2018
DOI: 10.1088/2058-8585/aab18a
|View full text |Cite
|
Sign up to set email alerts
|

Improved fine layer patterning using soft blanket gravure printing technology

Abstract: We have developed a 'soft blanket gravure' (SBG) printing technology that can form patterns onto curved or three-dimensional solid surfaces using functional ink. In SBG printing, a soft and thick blanket (called a 'soft blanket') is employed in the similar process to conventional gravure offset printing processes. We found and reported that SBG printing could completely receive silver ink from printing plates and transfer it to target substrates more effectively than conventional gravure offset printing under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…We designed and built a SBG printing system based on a conventional gravure offset printing technology. 29) In this initial prototype system and for this study, we used a plate-toplate printing configuration. In this system, the printing pressure was controlled by the compression depth of the soft blanket [Fig.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…We designed and built a SBG printing system based on a conventional gravure offset printing technology. 29) In this initial prototype system and for this study, we used a plate-toplate printing configuration. In this system, the printing pressure was controlled by the compression depth of the soft blanket [Fig.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Printing technology has emerged as a low-cost, environmental-friendly mass-manufacturing technology for the fabrication of next-generation printed flexible electronics devices. There are a number of printing methods that can be applied to biosensor fabrication, such as inkjet printing, [118][119][120][121][122][123] screen printing, 8,124 flexographic printing, 125,126 and gravure printing [127][128][129][130][131][132] (Fig. 6(a)).…”
Section: Advanced Printed Biosensor Systems Based On Flexible Hybrid mentioning
confidence: 99%
“…The SBR printer [shown in Fig. 1(e)], which was designed and constructed for our previous SBG printing studies as a prototype system with a plate-to-plate configuration, [20][21][22] was remodeled to add a coating base to which the slit coater could be fixed. The printer consists of a soft blanket roller that moves back and forth while rotating on two stages with fixed position and adjustable height.…”
Section: Sbr Printer Configuration and Printing Conditionsmentioning
confidence: 99%
“…In addition, our previous research showed that the conventional blanket was unable to change its surface into the grooves of a gravure printing plate under printing pressure. 22) This indicated that the conventional blanket could be applied to avoid contactdefects. Therefore, the soft blanket for SBR printing comprised a two-layered structure consisting of a thick and soft layer underneath a thin and hard layer (shown in Tables II).…”
Section: Characteristics Of the Soft Blanket And Other Components Of ...mentioning
confidence: 99%
See 1 more Smart Citation